Discounted Cash Flow Analysis and Real Options Valuation: A Case Study of Downstream Nickel Processing Investments in Indonesia - Nur Alim Kadir; Dzikri Firmansyah Hakam (Eduvest - Journal of Universal Studies, 2026)
This research evaluates the feasibility of processing nickel ore and refining it into nickel sulfate, while also assessing the potential for expansion into the production of battery precursor materials. The objective of this research is to provide a more comprehensive investment assessment framework by combining DCF and ROV for nickel down streaming projects, so that the results not only evaluate basic feasibility but also highlight the strategic value of managerial flexibility in dealing with uncertainty. The analysis employed a Discounted Cash Flow (DCF) approach for the base scenario, followed by Real Option Valuation (ROV) to capture the option value of the expansion. The DCF analysis results show a positive Net Present Value (NPV) of USD 1,164 million with an Internal Rate of Return (IRR) of 16.41%. Sensitivity analysis identifies nickel price, capital expenditure (CAPEX), and total resource availability as the most critical parameters affecting the project’s value. The novelty of this study lies in the application of ROV in the context of nickel mineral down streaming in Indonesia, which remains rarely explored in the literature compared to other energy sectors such as geothermal or hydropower. The contribution of this research is expanding the literature on the use of real options in the mining industry academically and offers a reference for investors, companies, and regulators to understand the strategic opportunities and risks of investing in nickel processing amid the growing global demand for electric vehicles  practically.